Research on Minority College Students’ Engagement in English Learning - Sun, Li (International Journal of Learning and Development, 2024)
This paper studies the relationship between minority college students’ English learning autonomy, English learning self-efficacy and English learning engagement, based on attribution theory and social cognitive theory. A questionnaire was first conducted on 570 ethnic minority non-English major college students in Yunnan province, Guizhou province, and Sichuan province, China. Then, statistical software is used to make regression analysis on the relationship between variables. Research results show that English learning autonomy has a significant positive impact on English learning engagement; English learning autonomy has a significant positive impact on English learning self-efficacy; English learning self-efficacy has a significant positive impact on English learning engagement; English learning self-efficacy has a partial mediating role in English learning autonomy and English learning engagement. Finally, some strategies are proposed to improve English learning engagement from motivation-driven perspective, involving learning evaluation, learning resources and learning guidance.